Buy now - pay later - Moss, John; Video Education Australasia (Bendigo, Victoria: Video Educational Australasia, 1998)
Shows a range of views on the advertising of food to teenagers and asking the following questions: why is there is so much food advertising during kid's show? how effective is it? should food producers have the right to advertise to such a vulnerable group
Executive producer, Neil Barrett ; camera Matt Fenney
Keywords: Advertising -- Food; Food -- Marketing; Children -- Nutrition